EP113/#78 Malignant peritoneal cytologic contamination with robotic hysterectomy for endometrial cancer. (4th December 2022) - Gwacham, Nnamdi; Kilowski, Karolina; Recio, Fernando; Awada, Ahmad; Patel, Ameya; Holloway, Jackson; Mckenzie, Nathalie; Ahmad, Sarfraz; Kendrick, James; Holloway, Robert
Abstract : Objectives: The aim of this study was to determine the prevalence of peritoneal cytologic contamination following robotic hysterectomy for EC. Methods: Peritoneal cytologies from the pelvis and diaphragm were obtained at the initiation of surgery, and from the pelvis only at the completion of robotic hysterectomy and sentinel lymph node mapping. Cytology specimens were processed and evaluated for the presence of malignant cells. Pre- and post-hysterectomy specimens were compared Results: 162 patients underwent robotic hysterectomy with sentinel lymph node mapping for EC with the use of a uterine manipulator. Mean age and body mass index were 65.9 ± 9.7 yr, and 34.1 ± 7.8 kg/m 2 . 34/162 (20.9%) cases had positive cytologies including 33 (20.4%) pelvic, 2 (1.2%) diaphragm. Pre-hysterectomy (+) washings were 12 pelvic, 0 diaphragm, and 2 both. Twenty (12.3%) patients had (+) cytology at hysterectomy completion after initially negative pre-hysterectomy cytologies. Six (3.7%) had conversion of positive cytology to negative following hysterectomy. Pelvic contamination was associated with deeper invasion (48.6% vs 29.7%, p=0.008), lesion size (4.71 cm vs 3.69 cm, p=0.03), positive pelvic lymph nodes (35.7% vs 10.4%, p=0.001), and presence of LVSI (50% vs 30.6%, p=0.03) Conclusions: Malignant peritoneal contamination occurred during robotic surgery for EC in 12% of cases. There was an association with lesion size, depth of invasion, positive pelvic lymph nodes, and LVSI. Whether or not peritoneal contamination leads to disease recurrence should be studied, including evaluation of patterns of recurrence and the potential impact of adjuvant therapies. Methods to reduce peritoneal contamination are likely warranted